2018
DOI: 10.1016/j.rvsc.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term shedding of Canine alphaherpesvirus 1 in naturally infected newborn pups

Abstract: The long-term shedding of Canine alphaherpesvirus 1 (CaHV-1) by neonatal pups with natural infection is reported. The pups belonged to a litter of 11 pointers of a breeding kennel in southern Italy, 9 of which developed a fatal form of systemic infection, as resulted by the detection of CaHV-1 in internal organs (kidney, liver, lung and brain) of one of this dogs and in the vaginal swab of their mother. The two remaining animals displayed a milder form of disease, with one pup showing ocular involvement, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…Compared to our results, other researchers have reported various prevalence of CHV-1 using molecular assays. Using real-time PCR technique, Losurdo reported that not only CHV-1 developed a fatal systemic illness clinically and histologically, but also it could result in long-term shedding of the virus through the nasal and ocular secretions and the faeces [3]. So, infected puppies pose a threat for other animals in the colony.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to our results, other researchers have reported various prevalence of CHV-1 using molecular assays. Using real-time PCR technique, Losurdo reported that not only CHV-1 developed a fatal systemic illness clinically and histologically, but also it could result in long-term shedding of the virus through the nasal and ocular secretions and the faeces [3]. So, infected puppies pose a threat for other animals in the colony.…”
Section: Discussionmentioning
confidence: 99%
“…Canine herpesvirus-1 (CHV-1), an alpha herpesvirus, is considered as a significant cause of neonatal deaths and reproductive problems in bitches with a widespread distribution [1][2][3]. In 1965, Carmichael et al described this pathogen for the first time [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus is responsible for fetal death, abortion, mummification, or stillbirth in pregnant bitches [11]. Moreover, respiratory disease, ocular signs, and genital lesions are also documented [5, [12][13][14]. Lifelong latent infection is associated with localization of CHV-1 to nerve ganglia following recovery [1].…”
Section: Introductionmentioning
confidence: 99%
“…Kapil, 2015 demonstrated the shedding of CHV-1 in the vaginal canal during parturition as a risk factor for newborn puppies[23]. Long-term shedding of CHV-1 in neonatal puppies was documented by Losurdo et al in 2018[13]. Immunosuppression following administration of systemic prednisolone to the latently infected adult dogs can also reactive the virus[5].ConclusionsConsidering the results of this study, it is demonstrated that CHV-1 is present in the southeast of Iran.CHV-1 is common in farm and breeding kennels and could pose a threat.…”
mentioning
confidence: 99%